Oculocardiac Reflex during Pupilloplasty under Peribulbar Block - Akshay Bhatiwal; Sagarika Aggarwal; Shalini Virani; Sanjeev Kumar; Parveen Rewri (Delhi Journal of Ophthalmology)
A 25-year-old healthy man developed sinus bradycardia during pupilloplasty under peribulbar anesthesia. During slippage of 3rd suture, the patient complained of uneasiness, lightheadedness, and nausea. His heart rate had fallen to 39/min in sinus rhythm. Intravenous atropine was injected, which improved patients’ symptoms and heart rate to baseline. Oculocardiac reflex (OCR) has not been reported with pupilloplasty so far. This case highlights that the risk of OCR is inconspicuous in ocular procedures under peribulbar anesthesia, and monitoring of heart rate and swift response is needed to avert adverse outcomes.